Anti-inflammatory effects of PGE2 in the lung: role of the EP4 receptor subtype. Issue 8 (4th May 2015) - Birrell, Mark A; Maher, Sarah A; Dekkak, Bilel; Jones, Victoria; Wong, Sissie; Brook, Peter; Belvisi, Maria G
Abstract : Background: Asthma and chronic obstructive pulmonary disease (COPD) are chronic inflammatory diseases of the airway. Current treatment options (long acting β-adrenoceptor agonists and glucocorticosteroids) are not optimal as they are only effective in certain patient groups and safety concerns exist regarding both compound classes. Therefore, novel bronchodilator and anti-inflammatory strategies are being pursued. Prostaglandin E2 (PGE2 ) is an arachidonic acid-derived eicosanoid produced by the lung which acts on four different G-protein coupled receptors (EP1–4 ) to cause an array of beneficial and deleterious effects. The aim of this study was to identify the EP receptor mediating the anti-inflammatory actions of PGE2 in the lung using a range of cell-based assays and in vivo models. Methods and results: It was demonstrated in three distinct model systems (innate stimulus, lipopolysaccharide (LPS); allergic response, ovalbumin (OVA); inhaled pollutant, cigarette smoke) that mice missing functional EP4 ( Ptger4 −/− ) receptors had higher levels of airway inflammation, suggesting that endogenous PGE2 was suppressing inflammation via EP4 receptor activation. Cell-based assay systems (murine and human monocytes/alveolar macrophages) demonstrated that PGE2 inhibited cytokine release from LPS-stimulated cells and that this was mimicked by an EP4 (but not EP1–3 ) receptor agonist and inhibited by an EP4 receptor antagonist. The anti-inflammatory effect occurred at the transcriptional level and was via the adenylyl cyclase/cAMP/ cAMP-dependent protein kinase (PKA) axis. Conclusion: This study demonstrates that EP4 receptor activation is responsible for the anti-inflammatory activity of PGE2 in a range of disease relevant models and, as such, could represent a novel therapeutic target for chronic airway inflammatory conditions.